CONNECTION BETWEEN GROUP CONFORMITY AND FREE SEX BEHAVIOR IN ADOLESCENCE - Trida Cynthia (Jurnal Psikologi, 2007)
The aim of this research is to test empirically the connection between group conformity and free sex in adolescence. The method was using 59 statements of group conformity scale and 60 statements of free sex behavior in adolescence. The score was giving depend on favorable and unfavorable statements. Coefficient validity for group conformity was from 0,2551-0,6274 and 0,8038 for coefficient reliability. Coefficient validity for free sex behavior in adolescence was from 0,3706-0,7953 and 0,9560 for coefficient reliability. There was a positive significant corelation between group conformity and free sex behavior in adolescence, subject who had a higher group conformity would possibly do free sex behavior, otherwise subject who had a lower group conformity possibly wouldn’t do free sex behavior.Keywords: group conformity, free sex behavior, adolescence